Global Poverty, A Matter of Justice or Charity? (Andamios, Revista de Investigación Social, 2014)
Several authors claim that citizens from rich countries have towards the global poor mere duties of beneficence, not duties of justice. This has important practical consequences. Citizens from rich countries have towards their own compatriots certain duties of justice.  Duties of justice should be prioritized over duties of beneficence.  Therefore, when duties of justice between compatriots conflict with duties of beneficence towards foreigners, the former have priority. This article identifies two necessary conditions to classify a duty as a duty of beneficence, and shows that the duties towards the global poor meet none of them. Moreover, this paper shows that the alleged priority of justice over beneficence is not true of all cases.
Keywords: Global poverty; duties; justice; beneficence; priority